[EMIM]AlCl4-ionic liquid catalyzed mechanochemically assisted green approach towards the synthesis of quinoxaline, 6H-indolo[2,3-b]quinoxaline and benzimidazole derivatives - Shafaque M. Shaikh; Gulafshan M. Ansari; Zobia Z. Karbari; Aditi A. Babre; Vikas V. Borge; Vikas M. Bangade; Damodara N. Kommi; Bhushan B. Popatkar (Results in Chemistry)
In the presented work, a convenient and effective methodology for the synthesis of quinoxaline, 6H-indolo[2,3-b]quinoxaline and benzimidazole derivatives has been developed. The reaction of 1,2-diamines with various substituted benzil, isatin and aldehydes produces quinoxaline, 6H-indolo[2,3-b]quinoxaline and benzimidazole derivatives respectively. The reaction between 1,2-diamines with various substituted benzils, isatins and aldehydes was carried out in presence of catalytic amount of [EMIM]AlCl4 (1-ethyl-3-methylimidazolium tetrachloroaluminate) ionic liquid in ethanol under the grinding condition in mortar and pestle. The ease of handling of catalyst, inclusion of eco-friendly solvent, attractive yield of the product, shorter reaction time and overall operational simplicity are some significant outcome of this procedure.